Can upfront DPYD extended variant testing reduce toxicity and associated hospital costs of fluoropyrimidine chemotherapy? A propensity score matched analysis of 2022 UK patients - Apostolos Tsiachristas; Grant Vallance; Rositsa Koleva-Kolarova; Harriet Taylor; Luke Solomons; Giovanni Rizzo; Catherine Chaytor; Junel Miah; Sarah Wordsworth; A. Bassim Hassan (BMC Cancer, 2022)
Abstract Aim To independently assess the impact of mandatory testing using an extended DPYD variant panel (ToxNav®) and consequent dose adjustment of Capecitabine/5-FU on recorded quantitative toxicity, symptoms of depression, and hospital costs. Methods We used propensity score matching (PSM) to match 466 patients tested with ToxNav® with 1556 patients from a historical cohort, and performed regression analysis to estimate the impact of ToxNav®on toxicity, depression, and hospital costs. Results ToxNav® appeared to reduce the likelihood of experiencing moderate (OR: 0.59; 95%CI: 0.45–0.77) and severe anaemia (OR: 0.55; 95%CI: 0.33–0.90), and experience of pain for more than 4 days a week (OR: 0.50; 95%CI: 0.30–0.83), while it increased the likelihood of mild neutropenia (OR: 1.73; 95%CI: 1.27–2.35). It also reduced the cost of chemotherapy by 12% (95%CI: 3–31) or £9765, the cost of non-elective hospitalisation by 23% (95%CI: 8–36) or £2331, and the cost of critical care by 21% (95%CI: 2–36) or £1219 per patient. For the DPYD variant associated with critical risk of toxicity (rs3918290), the improved non-elective hospital costs were > £20,000, whereas variants associated with hand-foot syndrome toxicity had no detectable cost improvement. Conclusion Upfront testing of DPYD variants appears to reduce the toxicity burden of Capecitabine and 5-FU in cancer patients and can lead to substantial hospital cost savings, only if the dose management of the drugs in response to variants detected is standardised and regulated.